2010
DOI: 10.1002/cphc.201000017
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Influence for the Zn‐tetraphenyl‐porphyrin Adsorption Geometry and the Interface‐Induced Electron Transfer

Abstract: In molecular devices, the importance of interfaces cannot be neglected as they determine charge injection and charge flow and, therefore, the device performance. Herein we report on the interaction of one single layer of Zn-tetraphenyl-porphyrin with Ag(110) and Si(111). Photoemission, near-edge X-ray absorption, and resonant photoemission are used to study the bonding nature, the adsorption geometry as well as the dynamics of electron transfer between the molecules and the metal or semiconductor surfaces. Mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 63 publications
9
44
0
Order By: Relevance
“…For ZnTPP on the more reactive Ag (1 1 0) surface, the appearance of the new valence state around 0.3-0.4 eV below E F was described and attributed to a transfer of electron density from the substrate to the complex, resulting in a partial occupation of the former molecular LUMO. The meso-phenyl rings of ZnTPP were found to interact more strongly with the substrate than the central porphin macrocycle [532]. A completely different bonding behaviour was observed for ZnTPP/Si (1 1 1), where the porphyrin macrocycle adsorbed with an angle of $ 151 relative to the substrate and interacted with the substrate mainly through the pyrrole rings of the porphyrin [532].…”
Section: Zinc Complexesmentioning
confidence: 82%
See 2 more Smart Citations
“…For ZnTPP on the more reactive Ag (1 1 0) surface, the appearance of the new valence state around 0.3-0.4 eV below E F was described and attributed to a transfer of electron density from the substrate to the complex, resulting in a partial occupation of the former molecular LUMO. The meso-phenyl rings of ZnTPP were found to interact more strongly with the substrate than the central porphin macrocycle [532]. A completely different bonding behaviour was observed for ZnTPP/Si (1 1 1), where the porphyrin macrocycle adsorbed with an angle of $ 151 relative to the substrate and interacted with the substrate mainly through the pyrrole rings of the porphyrin [532].…”
Section: Zinc Complexesmentioning
confidence: 82%
“…The Co ion, however, forms a strong bond to the N atoms of the surface nitride [386]. For ZnTPP on Si (1 1 1), it was found that electron transfer from the phenyl rings to the substrate is less favourable than on Ag (1 1 0) [532]. On rutile TiO 2 (1 1 0), it was found that CoPc is immobile at room temperature when adsorbed at 400 K with low flux and that the CoPc molecules introduce gap states at the surface.…”
Section: Adsorption On Non-metal Surfacesmentioning
confidence: 96%
See 1 more Smart Citation
“…A variety of techniques were used such as scanning tunneling microscopy (STM) to gain insight into adsorption geometries, near edge X-ray absorption fine structure (NEXAFS) to elucidate intramolecular features such as the relative orientation of the phenyl groups with respect to the macrocycle, 25,26,32,[40][41][42][43][44][45] Xray, 17,21,33,34,[37][38][39][41][42][43][44][45][46][47] ultraviolet, 17,28,34,40,46,47 and inverse 17,28,40 photoemission spectroscopy (XPS, UPS, and IPS) to probe directly the electronic structure and chemistry, and temperature programmed desorption (TPD) to track molecular desorption and hydrogen evolution with temperature. 27,33,48 On metal surfaces, due a strong porphyrin core iminic nitrogenssubstrate interaction, the mesophenyls are typically rotated and can even become coplanar with the porphyrin core.…”
Section: Introductionmentioning
confidence: 99%
“…For example in the case of ZnTPP (Zn-Tetra Phenyl Porphyrin) the molecule is terminated by four phenyl groups 16 and a Zn atom occupies the molecular center, coordinated by four equivalent N atoms. In a thick ZnTPP film the molecules interact by means of weak Van-der-Waals forces, thus maintaining a structure similar to the one they have in the gas phase 17 .…”
Section: Introductionmentioning
confidence: 98%